The Influence of Dietary Probiotic (Saccharomyces cerevisiae) Supplementation and Different Slaughter Age on the Performance, Slaughter and Carcass Properties of Broilers - Karaoglu, M.; Durdag, H. (International Journal of Poultry Science, 2005)
The present study was carried out to determine the influence of dietary probiotic (115-Biogallinox; containing Saccharomyces cerevisiae at 4 x 108 colony forming units/g) on growth, slaughter and carcass characteristics of broilers slaughtered at different ages (35, 42 and 49 days). Day-old male Ross-308 chicks (n = 336) were weighed and randomly assigned to three dietary treatment groups [P0 (control): 0 g probiotic/kg; P1: 1 g probiotic and P2: 2 g probiotic/kg] as a 3x3 factorial arrangement. Each treatment group was replicated eight times as subgroups, comprising of 14 birds each. The broiler chickens were grown on starter (0 to 21 days) and finisher (to 35, 42 and 49 days) diets calculated to meet NRC recommendations. Body weight and feed consumption were determined weekly during the study. Means to slaughter age of body weight, daily weight gain, daily feed consumption, feed efficiency and mortality were 2524.5, 50.7, 94.4 g, 1.86 and 1.8% for P0 group; 2559.1, 51.4, 94.8 g, 1.85 and 0.0% for P1 group; 2548.3, 51.2, 95.9 g, 1.88 and 1.8% for P2 group, respectively. None of the live performance variables investigated differed significantly between control and probiotic treatment. Similarly, probiotic treatment had no effect on the hot and cold carcass weight, carcass yield and the weight of carcass cuts and the abdominal fat pad. Means for these slaughter variables were 1543.8, 1521.3 g, 74.0, 73.4%, 31.0 g for P0 group; 1561.1, 1539.4 g, 74.2, 73.6%, 30.2 g for P1 group; 1558.7, 1535.2 g, 74.1, 73.5% and 31.0 g for P2 group, respectively. However, slaughter age had a highly significant effect on the final body weight slaughter variables mentioned above. In this experiment probiotic supplementation of broilers, up to the level of 4 x 108 colony forming units/kg feed, did not significantly affect the live performance and slaughter variables investigated.